Classroom Interaction on English for Nurses (EFN) Class - Putu Rusanti (FKIP Universitas Halu Oleo, 2020)
English for specific purposes or ESP is an approach for teaching English in other fields. Teaching English for Nurses (EFN) need sufficient effort since there are many terminologies related to nursing. The purpose of this study is to identify the types of classroom interaction on English for Nurses (EFN) class and to describe the students’ perception on classroom interaction during language interaction process on English for Nurses (EFN) class. This study used video recorder and questionnaires as the instrument to collect the data. The data were in the form of recording and interviewing. The result of the study found that the interaction involved teacher talk, students talk, and silence. Teacher talk consisted of accept feeling, praise and encourage the students, accept or uses ideas of students, ask question, lecturing, giving direction, criticizing or justifying authority. Students talk involved students talk response, students talk initiation, and silence. Based on the result of questionnaires, 42.3% of them agreed with the statement related perception on classroom interaction. It means that the students had positive response in the process of teaching and learning classroom.